Use of applications and rendering engines in architectural design – state-of-the-art - Borkowski, Andrzej; Nowakowski, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2023)
Computer methods in the AEC (Architecture, Engineering, Construction) industry are constantly evolving, mainly towards BIM, and the design process itself within an investment project focuses mainly on documentation. Visualisation or animation are optional elements, mostly done for sales purposes. Photorealism and the quality of created visualisations influence the impressions of the recipient, and the emotions evoked can determine a purchase or investment. As a rule, designers pay great attention to the visualisations they create, but they are not always aware of the solutions available on the market in this respect. In recent decades, rendering engines based on so-called real-time rendering have developed rapidly. The aim of the study was to provide a deep review of existing 3D modelling and visualisation solutions in terms of their popularity, applicability and advantages and limitations. The focus is on applications working with BIM software, which is widely used in the AEC industry. The paper attempts to compare the applications, lists their advantages, disadvantages, benefits and limitations in their use. The conclusions, sometimes subjective, can be useful for the whole community of architects and engineers, related to space design. The results of the review indicate the increasing popularity of 'real-time' solutions, which are displacing 'offline' solutions.